2010
DOI: 10.1258/shorts.2009.100056
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Foundation Programme Choice among Medical Students

Abstract: ObjectivesThe advent of Modernising Medical Careers has replaced the traditional pre-registration house officer (PRHO) year and first year of senior house officer (SHO) training with a combined foundation programme. The aim of this study was to find out the factors influencing choice of foundation programme among medical students.DesignProspective survey.SettingThree medical schools based in England.Main outcome measuresA questionnaire was formulated containing the reasons for choosing a foundation programme w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 3 publications
2
8
0
Order By: Relevance
“…This is in keeping with previous similar studies by Patel et al9 and McElvanna et al10 Social relationships in the form of partner and family were second and third, respectively.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is in keeping with previous similar studies by Patel et al9 and McElvanna et al10 Social relationships in the form of partner and family were second and third, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Our low response rate could have been addressed with a second wave of emails or providing paper-based questionnaires. Our study had a superior number of participants compared to the two previous studies9,10 (361 vs 149 [response rate=61%]10 and 46 [response rate unknown]9) and sampled of a greater percentage of medical schools (9 vs 110 and 39). Nevertheless, further studies should include a greater participant number from a more comprehensive number of foundation/medical schools.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Several attributes and levels are used to describe an alternative, and individuals’ stated choices are used to determine their preferences for changes in the attributes (see for further detail about DCEs within a medical education context). The DCE is used commonly in studies of the labour market choices of qualified health care professionals, although rarely with respect to doctors in training, and never, to the best of our knowledge, medical students (but see for the use of a DCE in students considering application to medical school). Our objective in using a DCE was to understand how medical students trade off different training position attributes when they choose their first training position.…”
Section: Methodsmentioning
confidence: 99%
“…In the UK, the first training position is an FP place, obtained via a national application and allocation system in which students rank specific programmes. Previous research has identified that the factors that influence medical careers decision making generally are also pertinent to FP preferences . However, we do not know which of these factors are most important.…”
Section: Introductionmentioning
confidence: 92%